2015
DOI: 10.5194/acp-15-8889-2015
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric ozone and its precursors from the urban to the global scale from air quality to short-lived climate forcer

Abstract: Abstract. Ozone holds a certain fascination in atmospheric science. It is ubiquitous in the atmosphere, central to tropospheric oxidation chemistry, yet harmful to human and ecosystem health as well as being an important greenhouse gas. It is not emitted into the atmosphere but is a byproduct of the very oxidation chemistry it largely initiates. Much effort is focused on the reduction of surface levels of ozone owing to its health and vegetation impacts, but recent efforts to achieve reductions in exposure at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
679
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,066 publications
(804 citation statements)
references
References 681 publications
19
679
1
8
Order By: Relevance
“…Tropospheric chemistry is a highly coupled system with significant interplay between the NO x , HO x , and RO x systems (Monks et al, 2015). Changes in the individual production and loss terms are relatively small, but halogens reduce net O 3 production by 194 Tg yr −1 in the present day and 145 Tg yr −1 in the preindustrial.…”
Section: Resultsmentioning
confidence: 99%
“…Tropospheric chemistry is a highly coupled system with significant interplay between the NO x , HO x , and RO x systems (Monks et al, 2015). Changes in the individual production and loss terms are relatively small, but halogens reduce net O 3 production by 194 Tg yr −1 in the present day and 145 Tg yr −1 in the preindustrial.…”
Section: Resultsmentioning
confidence: 99%
“…Although the stratospheric contribution to the O 3 concentrations at the surface is generally small (3-5 ppb(v)) in Europe (Lelieveld and Dentener, 2000), it can be a relevant contribution to near-surface O 3 in certain areas and time periods (Zanis et al, 2014) and could affect the observed trend in near-surface O 3 (e.g., Fusco and Logan, 2003). Despite the large number of studies of tropospheric O 3 , a number of challenges still remain, such as explaining the near-surface concentration trends (Monks et al, 2015).…”
Section: Andersson Et Al: Reanalysis Of and Attribution To Near-smentioning
confidence: 99%
“…Asian emissions have continued to rise under the same period (Ohara et al, 2007). Jonson et al (2006) showed that the trend in O 3 concentrations in Europe cannot be fully explained by changes in European precursor emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Isoprene oxidation fuels tropospheric ozone formation in both rural and urban regions (Monks et al, 2015), and isoprene oxidation products contribute significantly to organic aerosol (Carlton et al, 2009). Regional air-quality predictions are heavily dependent on isoprene emission estimates (Pierce et al, 1998;Fiore et al, 2005;Hogrefe et al, 2011;Mao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%